Makna Tradisi Kelo Fomate: Analisis Antropologis Perkawinan Suku Oenames-Kaesmetan di Wilayah Perbatasan RI-RDTL - Tamelab, Petrus; Duka, Gerardus B (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2026)
This study analyzes the shifting understanding of the Kelo Fomate tradition—a stage in the customary marriage rites of the Oenames and Kaesmetan tribes in Oepoli, a border region between Indonesia and East Timor—which is intended to preserve the sanctity of the marital bond. The main issue examined is the fading of the educational and essential values of this tradition in modern society. Using a qualitative method with a descriptive approach, this study discusses field data in relation to theological concepts of marriage. The results of the analysis indicate a decline in public understanding, as evidenced by the widespread phenomenon of young couples living together (kumpul kebo) and even having children before their union is legally recognized under customary and religious law. A discussion of the data and theory concludes that the shift in the values of the Kelo Fomate tradition has direct implications for the decline in the community’s awareness of and appreciation for the sanctity of marriage as a sacrament.